The effect of entrepreneurial orientation, innovation capability and knowledge creation on firm performance: A perspective on small scale entrepreneurs - Omar N.A.; Md Aris H.; Nazri M.A. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by Scopus